Transmission of Theileria parva to cattle by Rhipicephalus appendiculatus adults fed as nymphae in vitro on infected blood through an artificial membrane - Walladde, S.M.; Young, A.S.; Ochieng, S.A.; Mwaura, S.N.; Mwakima, F.N. (Cambridge University Press, 1993)
A technique is described for the efficient feeding of Rhipicephalus appendiculatus nymphae on cattle blood through an artificial membrane bearing tactile and olfactory stimuli. The effect of four anticoagulation methods on the feeding of nymphae was compared and heparinized blood was found to be the most efficacious, followed by defibrinated blood. Blood treated with acid citrate dextrose (ACD) or ethylenediamine tetraacetate (EDTA) inhibited nymphal feeding. Nymphae fed on heparinized and defibrinated blood obtained engorgement weights within the range of ticks fed on mammalian hosts and they subsequently moulted and fed normally as adults and produced viable eggs. Nymphae fed on membranes using either defibrinated or heparinized blood infected with Theileria parva piroplasms developed salivary gland infections as adult ticks and transmitted East Coast fever (ECF) to susceptible cattle. There were indications that T. parva-infected defibrinated blood was not as infective to the feeding nymphae as the infected heparinized blood. When T. parva-infected heparinized blood was used to feed nymphae through membranes in two experiments, it was found that the infections in the resultant adult ticks could be comparable to those of nymphae fed on donor cattle, but were usually lower. The membrane feeding technique will enable the study of factors affecting the tick and T. parva transmission without the complication of host/T. parva interactions and could be useful for both tick maintenance and Theileria parasite isolation and maintenance.